Some Cesaro-Type Summability Spaces of Order ? and Lacunary Statistical Convergence of Order ? - Et, Mikail; Sengul, Hacer (Univ Nis, Fac Sci Math, 2014)
In the paper [32], we have defined the concepts of lacunary statistical convergence of order ff and strong N-theta(p)-summability of order ff for sequences of complex (or real) numbers. In this paper we continue to examine others relations between lacunary statistical convergence of order alpha and strong N-theta(p)-summability of order alpha.
Keywords: Lacunary sequence; Statistical convergence; Modulus function